Production of Bioethanol from Agricultural Wastes Utilising Fermentation Potential of Saccharomyces cerevisiae - Hossain, Md. Sarower; Habib, Md. Ahasun; Saha, Sumitra; Akhtar, Fahmina; Yasmin, Sabina; Khatun, Fahmida (Journal of the Bangladesh Agricultural University, 2024)
The present study was designed to produce bioethanol from three lignocellulosic biomasses, such as sugarcane bagasse, rice straw and wheat straw utilising fermentation potential of Saccharomyces cerevisiae. After physical treatment, three substrates were pre-treated with 5% H2SO4 + 1% NaOH, followed by steaming at 121°C for 15 minutes. Then the substrates were hydrolysed by commercial alpha-amylase enzyme and fermented by S. cerevisiae under anaerobic and submerged conditions. Fermentation media were prepared at different pH (3.7, 3.9, 4 and 4.6) and the fermentation process was carried out at different temperature (37°C, 40°C and 45°C) and bioethanol yield was measured after different fermentation periods (72 hrs, 96 hrs, and 120 hrs) to investigate the effect of temperature, pH and fermentation period on bioethanol production. The highest bioethanol concentration (16.29%) was obtained from sugarcane bagasse when the pH of fermentation broth was 4.0 and the temperature was 40°C after 96 hours of the fermentation period. The lowest ethanol concentration (13.0%) was obtained from the wheat straw at pH 3.7 while the temperature was 37°C after 72 hours of the fermentation period. Among the tested substrates, sugarcane bagasse produced more bioethanol than that of rice straw and wheat straw by using the fermentation potential of S. cerevisiae. The result of the study suggested that agricultural wastes can be utilised as cost-effective substrates for bioethanol production. J Bangladesh Agril Univ 18(4): 975–981, 2020 https://doi.org/10.5455/JBAU.8647